2018
DOI: 10.1021/acs.chemmater.7b04619
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Capture of Perrhenate and Pertechnetate by a Mesoporous Zr Metal–Organic Framework and Examination of Anion Binding Motifs

Abstract: At the Hanford Site in southeastern Washington state, the U.S. Department of Energy intends to treat 56 million gallons of legacy nuclear waste by encasing it in borosilicate glass via vitrification. This process ineffectively captures radioactive pertechnetate (TcO4 –) because of the ion’s volatility, thereby requiring a different remediation method for this long-lived (t 1/2 = 2.1 × 105 years), environmentally mobile species. Currently available sorbents lack the desired combination of high uptake capacity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 128 publications
(81 citation statements)
references
References 62 publications
0
81
0
Order By: Relevance
“…3c , the sorption isotherm curves plotted by the equilibrium concentration against the ion-exchange capacity q (mg/g) are fit well with the Langmuir model and the maximum anion-exchange capacity ( q m ) was calculated to be 318 ± 8 mg/g (Supplementary Tables 3 and 4 ). This greatly exceeds the capacity of Yb 3 O(OH) 6 Cl (48.6 mg/g) 49 , NDTB-1 (49.4 mg/g) 49 , UiO-66-NH 3 + (159 mg/g) 48 , NU-1000 (210 mg/g) 47 , SCP-IHEP-1 (211 mg/g) 46 , SCU-101 (247 mg/g) 42 , and SCU-102 (291 mg/g) 45 , but is lower than those of SCU-CPN-1 (999 mg/g) 21 , SCU-100 (541 mg/g) 16 , SLUG-21 (602 mg/g) 39 , PAF-1-F (420 mg/g) 59 .…”
Section: Resultsmentioning
confidence: 89%
“…3c , the sorption isotherm curves plotted by the equilibrium concentration against the ion-exchange capacity q (mg/g) are fit well with the Langmuir model and the maximum anion-exchange capacity ( q m ) was calculated to be 318 ± 8 mg/g (Supplementary Tables 3 and 4 ). This greatly exceeds the capacity of Yb 3 O(OH) 6 Cl (48.6 mg/g) 49 , NDTB-1 (49.4 mg/g) 49 , UiO-66-NH 3 + (159 mg/g) 48 , NU-1000 (210 mg/g) 47 , SCP-IHEP-1 (211 mg/g) 46 , SCU-101 (247 mg/g) 42 , and SCU-102 (291 mg/g) 45 , but is lower than those of SCU-CPN-1 (999 mg/g) 21 , SCU-100 (541 mg/g) 16 , SLUG-21 (602 mg/g) 39 , PAF-1-F (420 mg/g) 59 .…”
Section: Resultsmentioning
confidence: 89%
“…The uptake capacities possessed clear dependence on the number of defect sites (i.e., not occupied by structural ligands). The capture of pertechnetate (TcO 4 − ) and perrhenate (ReO 4 − ) was shown to occur by a pseudo‐ion exchange mechanism at the hydroxyl or water‐capped sites in the Zr node of NU‐1000 by the same group . As an example of the second case (capture of coordinating organic ligands), Gu et al reported a superior uptake capacity of the organophosphorous pesticides, glyphosate, and glufosinate, by UiO‐67(Zr) .…”
Section: Environmental Applicationsmentioning
confidence: 99%
“…The activated samples were immersed in 0.05 m m ReO 4 − solution for 10 h, and the corresponding samples were centrifuged and washed by water to remove the attached ReO 4 − . Inductively coupled plasma (ICP) was performed to determine the adsorption mass of ReO 4 − ; this can reach 807 mg g −1 , which are falling among the highest values known for MOF (Table and S4) . Subsequently, to explore the selectivity of 1 for capturing ReO 4 − , 5 m m Cl − , OAc − and SO 4 2− were simultaneously mixed with 0.05 m m ReO 4 − solution.…”
Section: Figurementioning
confidence: 99%